2014
DOI: 10.4161/cc.29215
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of histone deacetylases enhances DNA damage repair in SCNT embryos

Abstract: Recent studies have shown that DNA damage affects embryo development and also somatic cell reprogramming into induced pluripotent stem (iPS) cells. It has been also shown that treatment with histone deacetylase inhibitors (HDACi) improves development of embryos produced by somatic cell nuclear transfer (SCNT) and enhances somatic cell reprogramming. There is evidence that increasing histone acetylation at the sites of DNA double-strand breaks (DSBs) is critical for DNA damage repair. Therefore, we hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 68 publications
(85 reference statements)
3
25
0
Order By: Relevance
“…Therefore, we hypothesized that CDK2 knockdown-induced cell cycle arrest may be caused by increased accumulation of DNA damage during early embryonic development. Indeed, by analyzing the number of γH2AX fluorescent foci [37,38], we demonstrated that CDK2 knockdown embryos have more DNA DSBs than control embryos on days 3 and 5 of development. In response to DNA damage, cell cycle checkpoints (G1, S, G2/M) are activated, stopping cell cycle progression to allow time for repair, thereby preventing transmission of damaged or incompletely replicated chromosomes [3].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we hypothesized that CDK2 knockdown-induced cell cycle arrest may be caused by increased accumulation of DNA damage during early embryonic development. Indeed, by analyzing the number of γH2AX fluorescent foci [37,38], we demonstrated that CDK2 knockdown embryos have more DNA DSBs than control embryos on days 3 and 5 of development. In response to DNA damage, cell cycle checkpoints (G1, S, G2/M) are activated, stopping cell cycle progression to allow time for repair, thereby preventing transmission of damaged or incompletely replicated chromosomes [3].…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, the HR pathway seems to be more important than the NHEJ pathway for DSB repair in embryonic stem cells (40). In early developing embryos, the two repair pathways are active (2, 41) and gene transcripts of the two pathways are up‐regulated in response to UV‐induced DNA damage (4, 6). Nonetheless, previous studies have not determined if both pathways play crucial roles in DSB repair during early embryo development, and whether there is a synergistic or compensatory activation of the response between the pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The same software was used to determine the number of DSBs by counting the number of H2AX139ph foci >0.3 μm 3 in each nucleus (37). We also counted the number of fluorescent foci for 53BP1 and RAD51 that colocalized with H2AX139ph foci (6).…”
Section: Scntmentioning
confidence: 99%
“…Many studies have showed that the developmental defects of cloned embryos fail to eliminate epigeneticspecific markers completely and establish the related gamete markers themselves (Kishigami et al, 2006;Latham, 2005;Rideout et al, 2001;Shi et al, 2003). Moreover, many studies also found that an abnormal epigenetic modification might result in the developmental failure of SCNT embryos, such as abnormal histone acetylation and DNA methylation in reprogramming (Bohrer et al, 2014;Enright et al, 2005;Jafarpour et al, 2011;Sangalli et al, 2014). Histone acetylation is a part of epigenetic modification (Grunstein, 1997;Turner, 2002) and is related to transcriptional activation by regulating the chromosome structure.…”
Section: Discussionmentioning
confidence: 96%